Policing with Contempt: The Degrading of Truth and Denial of Justice in the Aftermath of the Hillsborough Disaster. - Scraton, Phil (Journal of Law & Society)
The Hillsborough disaster happened at a premier United Kingdom soccer stadium in April 1989 claiming the lives of ninety-six men, women, and children. Over the next decade there followed a Home Office inquiry, a criminal investigation, compensation hearings as far as the House of Lords, the longest inquests in recent history, a judicial review, a judicial scrutiny, and private prosecutions. Media coverage has remained intense and there has been persistent parliamentary debate. Despite the evidence amassed, much of it undisclosed, the legal argument and official discourse, the bereaved and survivors remain deeply concerned that the `truth' of Hillsborough has been suppressed and reconstructed. This paper considers Hillsborough and its long-term aftermath in the context of a theoretical discussion of the reconstitution and registration of `truth' within social democracies when state institutions stand accused. It adopts a critical analysis drawing on human rights discourse in discussing how `regimes of truth' operate to protect and sustain the interests of the `powerful'. In examining the formal legal processes and their outcomes regarding Hillsborough, the paper demonstrates how they were manipulated to degrade the truth and deny justice to the bereaved. In revealing the procedural and structural inadequacies of these processes, the paper raises fundamental questions about the legal and political accountability of the police. Finally, it discusses alternative forms, informed by a human rights agenda, through which `truth' can be acknowledged and institutionalized injustices reconciled.